Antiviral properties of silver nanoparticles against norovirus surrogates and their efficacy in coated polyhydroxyalkanoates systems. (June 2017) - Castro-Mayorga, J.L.; Randazzo, W.; Fabra, M.J.; Lagaron, J.M.; Aznar, R.; Sánchez, G.
Abstract: Silver nanoparticles (AgNP) have strong broad-spectrum antimicrobial activity and gained increased attention for the development of AgNP based products, including medical and food applications. Initially, the efficacy of AgNP and silver nitrate (AgNO3 ) was evaluated for inactivating norovirus surrogates, the feline calicivirus (FCV) and the murine norovirus (MNV). These norovirus surrogates were exposed to AgNO3 and AgNP solutions for 24 h at 25 °C and then analyzed by cell-culture assays. Both AgNP and silver ions significantly decreased FCV and MNV infectivity in a dose-dependent manner between concentrations of 2.1 and 21 mg/L. Furthermore, poly (3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) films were prepared by depositing a coating of thermally post-processed electrospun PHBV18/AgNP fiber mats over compression moulded PHBV3 films. After 24 h exposure at 37 °C and 100% RH, no infectious FCV were recovered when in contact with the AgNP films while MNV titers decreased by 0.86 log. The morphology of the PHBV18 and PHBV18/AgNP fibers studied by SEM showed smooth and continuous fibers in both cases and the EDAX analysis confirmed the homogeneously distribution of AgNP into the coating and onto the PHBV3/PHBV18 layer. This study showed, for the first time, the suitability of the PHBV18/AgNP electrospun coating for antiviral surfaces. Highlights: Antiviral activity of AgNPs and AgNO3 was evaluated on MNV and FCV. Both significantly decrease FCV and MNV infectivity in a dose-dependent manner. A PHBV18/AgNPs electrospun coating was produced. The AgNP electrospun coating completely inactivated FCV based on ISO 22196:2011.